(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the level of knowledge and analyze associated factors regarding pressure ulcer prevention among nurses at Transport Hospital in 2024. Methods: A cross-sectional descriptive study was conducted among 86 clinical nurses using the standardized PUKT questionnaire. Data were analyzed with SPSS 26.0. Results: The mean knowledge score was 42.34/47 (SD=2.11), with 97.67% of nurses achieving good to excellent levels. No statistically significant associations were found between knowledge and demographic variables (p>0.05). Conclusion: Nurses at Transport Hospital demonstrated high knowledge of pressure ulcer prevention. However, certain specific aspects require further reinforcement through continuous education and training programs.